Evolution of Smart Grids - Fadlullah, Zubair Md.; Kato, Nei.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This SpringerBrief explores the opportunities and challenges posed by the smart grid. The evolution of the smart grid should allow consumers to directly communicate with their utility provider. However, complex issues such as architecture with legacy support, varying demand response and load management, varying price of power, and so forth can lead to various decision making challenges. It is essential to identify the scope and challenges of the smart grid in a comprehensive manner so as to ensure efficient delivery of sustainable, economic, and secure electricity supplies. This book provides an overview of the smart grid and its key advances in architecture, distribution management, demand-side response and load balancing, smart automation, electric storage, power loss minimization and security. Readers interested in a basic knowledge of electric grid and communication networks will find Evolution of Smart Grids useful. Readers who want more insight on smart grid research will also find this book a valuable resource. .
Introduction -- Considered smart grid model -- Challenges in Smart Grid -- Demand Response Challenge in Smart Grid -- Game Theoretic Coalition Formulation Strategy for Reducing Power Loss in Micro Grids -- On Optimally Reducing Power Loss in Micro-Grids with Power Storage Devices -- A Distributed Paradigm for Power Loss Reduction in Micro-Grids -- Security Challenge in the Smart Grid -- Conclusion and Future Directions. .
Keywords: Computer Communication Networks; Information systems; Telecommunication; Computer Communication Networks; Information Systems and Communication Service; Communications Engineering, Networks